Una estrategia didáctica: el aprendizaje del pasado simple en francés por medio de los cuentos e Internet - Daniel Cersosimo, Emilie Michele (2014)
In this article we made a description of a didactic strategy used in the class LM-2121 Integrated French II, in order to learn the simple past in French with short stories and Internet. We analyze the importance of constructivism and the technology implementation in the teaching-learning process.